Coral reefs & global climate change : potential contribution of climate change to stresses on coral reef ecosystems - Buddemeier, Robert W. (Pew Centre on Global Climate Change ArlingtonUS, 2004)
Analyzes the current state of knowledge regarding coral reef communities and the potential contribution of future climate change to coral reef degradation and loss.